Răspuns :
a+b+c=61
a:b=6 rest 3 => a=b*6+3;
c:b=1 rest 2 => c=b*1+2;
6b+3+1b+2+b=61;
8b+5=61;
8b=61-5;
8b=56;
b=56:8;
b=7;
7*6+3=42+3
=45 (a);
7*1+2=7+2
=9 (c).
a + b + c = 61
a : b = 6, r3 ⇒ a = 6b + 3
c : b = 1, r2 ⇒ c = b + 2
a + b + c = 61
6b + 3 + b + b + 2 = 61
8b + 5 = 61
8b = 61 - 5
8b = 56
b = 56 : 8
b = 7
a = 6b + 3
a = 7 · 6 + 3
a = 42 + 3
a = 45
c = b + 2
c = 7 + 2
c = 9
//
a : b = 6, r3 ⇒ a = 6b + 3
c : b = 1, r2 ⇒ c = b + 2
a + b + c = 61
6b + 3 + b + b + 2 = 61
8b + 5 = 61
8b = 61 - 5
8b = 56
b = 56 : 8
b = 7
a = 6b + 3
a = 7 · 6 + 3
a = 42 + 3
a = 45
c = b + 2
c = 7 + 2
c = 9
//